An Active Role Of An Independent Indian Judiciary In Interpreting Laws: A Comprehensive Study (Journal of Namibian Studies : History Politics Culture, 2022)
Present research seeks to analyse the role of one of the pillars of the democracy i.e., the independent judiciary in relating prevailing laws with present day scenario and enforcing the Laws in India, including landmark judgments and also the concept of judicial activism, distribution of powers between the various organ. “Judiciary is one of the three organs of the state. The function of independent judiciary is to provide justice based on the law of the land and other prevailing laws which are running as an undercurrent from the Constitution of the country. In India, there is a concept related to checks and balance of powers between the three organs. So, this separation of power is based on the distribution of powers as well as responsibilities of state into distinct branches and clearly defining their premises and so that its misuse is avoided. In India the concept of independent Judiciary is important to protect the people against capricious, tyrannical and whimsical powers of the state.” “When the legislative and executive powers are united in the same person, then there are greater chances to its misuse and there can be no liberty. Again, there is no liberty if the judicial power is not separated from the legislative and executive power. Where it joined with the legislative power, the life and liberty of the subject would be exposed to arbitrary control, for the judge would then be the legislator. Where it joined with the executive power, the judge might behave with violence and oppression then there would be end of everything was the same man or the same body to exercise these three powers.”  So, there should be a balance between all three organs of the state to provide social justice to the people of the country.